2018
DOI: 10.1088/1361-6528/aae7f3
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering magnetic hyperthermia properties of compositionally and morphologically modulated FeNi nanoparticles using first-order reversal curve analysis

Abstract: Magnetic hyperthermia based on nanoparticles (NPs) is considered a significant approach in cancer therapy. However, less attention has been paid to the correlation between hyperthermia properties and detailed magnetic characteristics. Herein, the hyperthermia capability of FexNi100-x (8 ≤ × ≤ 40) NPs synthesized using a polyol method was studied by investigating the temperature rise and specific loss power (SLP) of their ferrofluid (FF) solutions while also performing first-order reversal curve (FORC) analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…A different strategy to modulate the magnetic properties of MNPs consists of the modification of their internal composition. Several magnetic materials such as iron carbides, 78 iron−platinum, 79 or iron−nickel 80 have been prepared in the form of nanoparticles. However, as mentioned above, iron oxide-based MNPs are the most commonly used due to their easy/cheap synthesis and low toxicity degree, so here we will focus in the modification of the composition of these kinds of MNPs.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…A different strategy to modulate the magnetic properties of MNPs consists of the modification of their internal composition. Several magnetic materials such as iron carbides, 78 iron−platinum, 79 or iron−nickel 80 have been prepared in the form of nanoparticles. However, as mentioned above, iron oxide-based MNPs are the most commonly used due to their easy/cheap synthesis and low toxicity degree, so here we will focus in the modification of the composition of these kinds of MNPs.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…FeNi NPs were proposed as magnetic hyperthermia agents with an enhanced heat dissipation capability. 66 Since the composition, especially the ratio of elements in the nanocrystal, affects its characteristics, the magnetic properties of NPs with different Fe x Ni 100− x compositions (80 ≤ x ≤ 40) were analysed. 66 Alloy NPs with the required elemental ratio were prepared via a typical polyol process.…”
Section: Bimetallic Npsmentioning
confidence: 99%
“…66 Since the composition, especially the ratio of elements in the nanocrystal, affects its characteristics, the magnetic properties of NPs with different Fe x Ni 100− x compositions (80 ≤ x ≤ 40) were analysed. 66 Alloy NPs with the required elemental ratio were prepared via a typical polyol process. Iron( ii ) chloride and nickel( ii ) chloride were added to propylene glycol for further dissolution (170 °C).…”
Section: Bimetallic Npsmentioning
confidence: 99%
“…11,12 Originating from the popularity of innocuous iron oxides, Fe NPs were a natural first choice and their smaller size and improved magnetic properties have suggested that iron-based magnetic carriers would be superior to the existing maghemite and magnetite NPs. 13 Combinations of Fe with other metals, such as FePt, [14][15][16] FeNi, 17,18 and FeCo [19][20][21] nanoalloys, also appeared attractive. However, the high magnetic moment of cobalt NPs gives them an intrinsic advantage over the aforementioned materials, which can be exploited specifically in mNPH, where a combination of magnetisation and small diameters is crucial for the desired performance.…”
Section: Introductionmentioning
confidence: 99%